2008
DOI: 10.1200/jco.2007.14.8288
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Randomized Phase II Study of the Combination of Sorafenib and Dacarbazine in Patients With Advanced Melanoma: A Report From the 11715 Study Group

Abstract: Sorafenib plus dacarbazine was well tolerated in patients with advanced melanoma and yielded an encouraging improvement in PFS. Based on these findings, additional studies with the combination are warranted in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(146 citation statements)
references
References 30 publications
4
139
1
2
Order By: Relevance
“…Considerable preclinical evidence has associated the BRAF V600E mutation with heightened sensitivity to pharmacologic inhibition of RAF or MEK kinases (4,5). Although early clinical trials of RAF and MEK inhibitors failed to show a substantial benefit (6,7), recent phase I studies of selective RAF inhibitors have shown promising results in patients with BRAF-mutant tumors (8,9). Thus, optimizing therapeutic efficacy while avoiding or bypassing the emergence of resistance to MAP kinase pathway inhibition will likely gain increasing importance in melanoma and other MAP kinasedriven cancers.…”
mentioning
confidence: 99%
“…Considerable preclinical evidence has associated the BRAF V600E mutation with heightened sensitivity to pharmacologic inhibition of RAF or MEK kinases (4,5). Although early clinical trials of RAF and MEK inhibitors failed to show a substantial benefit (6,7), recent phase I studies of selective RAF inhibitors have shown promising results in patients with BRAF-mutant tumors (8,9). Thus, optimizing therapeutic efficacy while avoiding or bypassing the emergence of resistance to MAP kinase pathway inhibition will likely gain increasing importance in melanoma and other MAP kinasedriven cancers.…”
mentioning
confidence: 99%
“…Systematic search of the literature de-novo: [458,481,483,[486][487][488][489][490][491][492][493][494][495][496][497][498][499][500][501] Strength of consensus: 85 % RCT = randomized clinical trial, Ipi = ipilimumab, gp100 = vaccine, HR = hazard ratio, CI = confidence Interval, vs. = versus, sign. = significant, n.s.…”
Section: Level Of Evidence 1bmentioning
confidence: 99%
“…34 In a phase II trial, oral sorafenib (400 mg twice a day) and IV dacarbazine (1000 mg/m 2 on day 1 of a 21-day cycle) showed a 50% improvement in progression-free survival as compared to placebo plus dacarbazine. 35 However, overall survival was not improved. Additional investigations are ongoing.…”
Section: Fibrohistiocytic Tumorsmentioning
confidence: 99%